Quality of Life in Persons with Intellectual Disabilities and Mental Health Problems: An Explorative Study - Filip Morisse; Eleonore Vandemaele; Claudia Claes; Lien Claes; Stijn Vandevelde (The Scientific World Journal)
The field of intellectual disability (ID) is strongly influenced by the Quality of Life paradigm (QOL). We aimed at investigating whether or not the QOL paradigm also applies to clients with ID and cooccurring mental health problems. This paper aims at stimulating a debate on this topic, by investigating whether or not QOL domains are universal. Focus groups with natural and professional network members were organized to gather qualitative data, in order to answer two questions: (1) Are the QOL dimensions conceptualized in the model of Schalock et al. applicable for persons with ID and mental health problems? (2) What are indicators relating to the above-mentioned dimensions in relation to persons with ID and mental health problems? The results offer some proof for the assumption that the QOL construct seems to have universal properties. With regard to the second question, the study revealed that the natural and professional network members are challenged to look for the most appropriate support strategies, taking specific indicators of QOL into account. When aspects of empowerment and regulation are used in an integrated manner, the application of the QOL paradigm could lead to positive outcomes concerning self-determination, interdependence, social inclusion, and emotional development.